2009
DOI: 10.1016/j.ejcts.2009.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ischaemic conditioning of the stomach may reduce gastric-conduit morbidity following total minimally invasive oesophagectomy☆

Abstract: In this non-randomised clinical setting, our results suggest that ischaemic conditioning of the stomach prior to MIO is safe. There is a trend to reduced morbidity related to gastric-conduit ischaemia, which was demonstrated by a CUSUM analysis. A randomised trial is needed before ligation of the left gastric artery can be routinely recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…Our initial series of ligation 2 weeks preoperatively resulted in an apparent reduction of ischemic complications, as analyzed by Cumulative Sum (CUSUM) [29]. However we had some concerns about adhesions at definitive surgery (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Our initial series of ligation 2 weeks preoperatively resulted in an apparent reduction of ischemic complications, as analyzed by Cumulative Sum (CUSUM) [29]. However we had some concerns about adhesions at definitive surgery (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Akiyama in 1992 [27] reported the first human clinical series, and more recent studies have confirmed a beneficial impact of conditioning [28][29][30][31][32][33][34]. We adopted the practice, and in our own series have reported a decrease in the incidence of GCF [35]. Two weeks seems to be the optimal timing for ischemic conditioning [36].…”
Section: Introductionmentioning
confidence: 75%
“…As a consequence, we adopted two technical modifications aimed at reducing gastric conduit failure: (1) ischemic conditioning of the stomach by ligation of the left gastric artery 2 weeks before esophagectomy [5,6] and (2) use of a hand port to exteriorize the stomach and fashion an extracorporeal conduit. These key modifications (Fig.…”
Section: Resultsmentioning
confidence: 99%